Remoção de nitrogênio em biofiltros aerado e anóxico, com alto índice de vazios e sem remoção de lodo - Bezerra Filho, Weliton Freire (2011)
The improper disposal of nitrogen in receiving water courses causes problems such as toxicity to living beings through the consumption of oxygen to meet the nitrogen demand, eutrophication and nitrate contamination of aquifers. For this reason it is often necessary to be carried out complementary treatment of wastewater to eliminate or reduce the concentration of this compound in the wastewater. The objective of this study is to evaluate the biological removal of nitrogen compounds using submerged aerated and anoxic filters as post-treatment of an anaerobic system, with low cost and innovative technology, which in previous studies has shown high removal efficiency of organic matter and great potential biological nitrogen compounds removal. The simple design with perforated hoses for air distribution and filling with plastic parts proved to be very efficient in relation to organic matter removal and nitrification. The system presented, in the best stage, efficiency in converting ammonia to nitrate by 71%, and produced a final effluent concentration below 10 mg / L of NH3-N. In addition, carbon concentration was removed by 77%, producing final effluent with 24 mg/L COD. However, denitrification in anoxic filter was not effective even with the addition of an external carbon source. There was a reduction of up to 56% of nitrogen caused by the process of simultaneous nitrification and denitrification (SND). The high voids space presented by this type of support material coupled with direct aeration of the sludge, allows the respiration of biomass retained between the endogenous phase, increased cell retention time and sludge retention capacity, producing a final effluent with turbidity less than 5 UT and total suspended solids around 5.0 mg/L